The woman who fought an empire : Sarah Aaronsohn and her Nili spy ring - Wallance, Gregory (Potomac Books, An imprint of the University of Nebraska Press, 2018)
"The Woman Who Fought an Empire" tells the improbable odyssey of a spirited young woman--the daughter of Romanian-born Jewish settlers in Palestine--and her journey from unhappy housewife to daring leader of a notorious Middle East spy ring